PENGARUH WEBSITE DESIGN DAN BRAND AWARENESS TERHADAP PURCHASE INTENTION PENGGUNA SHOPEE DI SURABAYA - Rafli, Mohammad; Kharisma, Fresha; Rahman, Muhammad Fajar Wahyudi; Arifah, Ika Diyah Candra (Politeknik Negeri Ambon, 2026)
Introduction: This study examines how website design and brand awareness influence purchase intention among Shopee users in Surabaya, Indonesia, given the intense competition among e-commerce platforms and the need to understand key drivers of consumers’ buying decisions. Methods: A quantitative explanatory design was employed using an online questionnaire survey. Respondents were Shopee users residing in Surabaya, aged 17–40 years, and had made purchases on Shopee within the last year. The sample was selected through purposive sampling, and the analysis applied Structural Equation Modelling–Partial Least Squares (PLS-SEM) by assessing both the measurement model (reliability and validity) and the structural model (path significance and explained variance).Results: The findings show that brand awareness has a positive and significant effect on purchase intention (O = 0.656; t = 6.763; p = 0.000), while website design has a positive but non-significant effect (O = 0.172; t = 1.806; p = 0.072). The model explains a moderate proportion of variance in purchase intention (R² = 0.588), indicating that brand-related factors play a more decisive role than interface design in shaping purchase intentions on an established marketplace platform.Conclusion and suggestion: Overall, the results indicate that brand awareness is the key factor influencing purchase intention among Shopee users in Surabaya, while website design shows a positive but non-significant effect. Therefore, strengthening brand awareness should be prioritized, supported by maintaining an adequate website design to ensure a positive user experience. Keywords: Brand Awareness, Purchase Intention, Website Design